Photosynthetic response to water stress of the main grass species of southern patagonian steppe, Argentina - Peri, Pablo Luis; Gyenge, Javier; Fernandez, María Elena (Elsevier, 2024)
Comparative studies of basic physiological performance are needed to give insight of how grass species survive and grow under current and more severe drought predicted in the framework of climate change in arid steppe grasslands. In this study, photosynthetic performance and stomatal conductance (gs) were measured in leaves of six main grass species of southern Patagonian steppe, after exposing plants to different conditions of water availability. There was a negative linear relationship between photosynthesis at light saturation (Pmax) and plant water stress, expressed as pre-dawn leaf water potential (ψpd), mainly explained by the reduction in gs. A negative linear relationship was also observed between the photosynthetic efficiency (α) and the ψpd of plants, but only under moderate to severe water stress conditions. Grass species had different response to water stress graded in the following order: Pappostipa chrysophylla > Festuca gracillima > Rytidosperma virescens > Poa dusenii > Bromus setifolius. These results can assist to understand the natural spatial distribution of these species under arid conditions, to predict their performance under changing climate, and to select proper species for restoration plans in steppe grasslands.